2011
DOI: 10.1603/me10253
|View full text |Cite
|
Sign up to set email alerts
|

Productive Container Types for Aedes aegypti Immatures in Mérida, México

Abstract: During 2007-2010, we examined which container types in Mérida, México, are most productive for Aedes aegypti (L.) immatures. Surveys for mosquito immatures followed routine surveillance methodology and container type classifications used by Servicios de Salud de Yucatán. Our main findings were that (1) small and larger discarded containers that serve no particular purpose and therefore can be removed from the environment contribute strongly to larval and pupal production in Mérida, and (2) the importance of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 41 publications
6
41
1
4
Order By: Relevance
“…Methods used to collect mosquitoes and the classification of container types have been described in previous studies (Nájera-Vázquez et al 2004;García-Rejón et al 2011). Nets, turkey basters, or pipettes were used to collect immatures from water-holding containers.…”
Section: Sampling Of Immature and Adult Mosquitoesmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods used to collect mosquitoes and the classification of container types have been described in previous studies (Nájera-Vázquez et al 2004;García-Rejón et al 2011). Nets, turkey basters, or pipettes were used to collect immatures from water-holding containers.…”
Section: Sampling Of Immature and Adult Mosquitoesmentioning
confidence: 99%
“…Aedes aegypti mosquitoes are common in Yucatán State, and larvae and pupae are often found inside disposable containers, buckets, tires, flower pots, vases, and stormwater drains/catch basins where present (Winch et al 1992;García-Rejón et al 2011;Arana-Guardia et al 2014). Aedes aegypti occurs in a diverse range of habitats including residential premises, vacant lots, parking lots, and cemeteries (Baak-Baak et al 2014a,b).…”
mentioning
confidence: 99%
“…Surveys for immatures and classification of container types were as described in previous studies (Najera-Vazquez et al 2004, García-Rejón et al 2011a) and included inspection of potential development sites for immatures in homes and their patios and yards, on streets/sidewalks - primarily in storm-water drains/catch basins - and in the other targeted settings (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported on the immature or adult stage of the primary local vector mosquito, Aedes ( Stegomyia ) aegypti (L.), for dengue virus. The studies reported on containers and seasonal patterns of abundance for immatures (Lloyd et al 1992; Winch et al 1992; Manrique-Saide et al 2008, 2012, 2013; García-Rejón et al 2011a; Arana-Guardia et al 2014; Baak-Baak et al 2014) and examined different indoor environments for adults (García-Rejón et al 2008, 2011b). Additional studies have reported more broadly on the mosquito fauna of the Yucatán Peninsula (Najera-Vazquez et al 2004, Zapata-Peniche et al 2007, Ortega-Morales et al 2010, García-Rejón et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation